2016
DOI: 10.1016/j.micinf.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of atorvastatin on high fat diet induced survival during acute Chagas disease

Abstract: Chagasic cardiomyopathy, which is seen in Chagas Disease, is the most severe and life-threatening manifestation of infection by the kinetoplastid Trypanosoma cruzi. Adipose tissue and diet play a major role in maintaining lipid homeostasis and regulating cardiac pathogenesis during the development of Chagas cardiomyopathy. We have previously reported that T. cruzi has a high affinity for lipoproteins and that the invasion rate of this parasite increases in the presence of cholesterol, suggesting that drugs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Another aspect is that AVA displayed a low cardiotoxicity profile, which is a favorable characteristic since the heart is one of the main targets of T. cruzi infection and inflammation in CD (12). Our data corroborate in part the literature data demonstrating the beneficial cardiovascular pleiotropic effect of statins, such as AVA (2,3,22).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another aspect is that AVA displayed a low cardiotoxicity profile, which is a favorable characteristic since the heart is one of the main targets of T. cruzi infection and inflammation in CD (12). Our data corroborate in part the literature data demonstrating the beneficial cardiovascular pleiotropic effect of statins, such as AVA (2,3,22).…”
Section: Discussionsupporting
confidence: 86%
“…Also, the target product profile (TPP) for CD recommends analysis against both relevant parasite forms for mammalian hosts (trypomastigotes and intracellular forms) and examination of the effects on representatives of different T. cruzi DTUs (20). Although de Souza and Rodrigues (21) suggested AVA as a promising ergosterol biosynthesis inhibitor (EBI) in their 2009 review of sterol pathways as targets for antitrypanosomatid drugs, few studies have been performed to test the effects of statins on animal T. cruzi infection, and they revealed controversial data (17,22). Thus, due to the well-known pleiotropic profile of AVA acting as an antiparasitic agent, we conducted a repurposing study using this molecule, taking into consideration the phenotypic steps suggested for a novel anti-T. cruzi entity (23).…”
Section: Discussionmentioning
confidence: 99%
“…An RT 2 Profiler (SA Biosciences, Valencia, CA) custom designed PCR array for mouse genes involved in lipid metabolism, oxidative stress and inflammatory signaling was used to analyze gene expression. Data analysis was performed normalized to the expression of 18sRNA using the ∆∆CT method according to the manufacturer’s protocol (SABiosciences) and as previously mentioned [14, 21].…”
Section: Methodsmentioning
confidence: 99%
“…Data were pooled and statistical analysis was performed using a Student’s t-test (Microsoft Excel) as appropriate and significance differences were determined as p values between < 0.05 and <0.001 as appropriate. Gene array analyses were done in duplicates as described earlier [14, 21].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the patient’s medication intake before infection, some reports have evaluated the relationship between the medications and T. cruzi infection. Zhao et al [30] observed that in murine models, atorvastatin resulted in the overexpression of low-density lipoprotein (LDL) receptors, enhancing the number of parasites in tissues, inflammation and heart tissue damage, associated with high mortality rates during acute T. cruzi infection. Furthermore, Nagajyothi et al [31] observed that LDL receptors play an important role in the internalization of the parasite.…”
Section: Discussionmentioning
confidence: 99%